1995
DOI: 10.1515/cclm.1995.33.7.405
|View full text |Cite
|
Sign up to set email alerts
|

Dual Porphyria of Coexisting Variegata and Cutanea Tarda

Abstract: Summary:While porphyria cutanea tarda and porphyria variegata are independent diseases, we report on seven rare cases with a coincidence of these two different porphyrias in one Individuum.The mutual clinical symptom was a cutaneous photosensitivity, which is a major symptom in porphyria cutanea tarda and a facultative one in porphyria variegata. Additionally, five patients had also experienced episodes of acute abdominal pain, which were in three cases accompanied by neurological symptoms, thus offering evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Variegate porphyria occurs worldwide, but the highest prevalence has been reported from South Africa (5). Handa et al (4) first reported a case of variegate porphyria from India in 1975, following which there have been no more reports of this rare metabolic disorder from the Indian subcontinent, although a few cases of dual porphyria of variegate and porphyria cutanea tarda were reported earlier (6). Lack of positive family history indicates sporadic occurrence of this rare genetic disorder in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Variegate porphyria occurs worldwide, but the highest prevalence has been reported from South Africa (5). Handa et al (4) first reported a case of variegate porphyria from India in 1975, following which there have been no more reports of this rare metabolic disorder from the Indian subcontinent, although a few cases of dual porphyria of variegate and porphyria cutanea tarda were reported earlier (6). Lack of positive family history indicates sporadic occurrence of this rare genetic disorder in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…In the dual porphyrias, laboratory tests indicate the simultaneous deficiency of two enzymes along the haeme biosynthetic pathway either in one individual or within one family. To date, approximately 15 patients and families with this constellation have been reported (18–33), indicating that these porphyria variants are very rare, although some authors already raised the question 20 years ago whether this peculiar form of porphyria is underdiagnosed (34).…”
Section: Dual Porphyriasmentioning
confidence: 99%
“…Especially the combination of PCT with acute intermittent porphyria (AIP) or PV has been described [6]. Both dual porphyrias show the typical porphyrin patterns and clinical aspects of each of the involved porphyrin disorders.…”
Section: Classification Of Pctmentioning
confidence: 99%